46, XY DSD (Disorder of Sex Development) : Diagnosis dan Tatalaksananya. - Mildi Felicia; Beto Suhartono (Fakultas Kedokteran Universitas Kristen Indonesia, 2021)
Disorder of Sex Development (DSD) is a congenital disorder that occurs in the development of chromosomes, gonads, and internal or external genital organ. DSD of 46 XY is a condition where the children with XY genotype is not able to have complete virilization of external genital. Determination phase is an initial phase of reproductive system development. Disruption of this phase may potentially lead to DSD. Optimal care for children with Disorder of Sex Development requires a multidisciplinary team starting since neonatal period. Family and pregnancy history, complete physical examination and assessment of genital organ are the first step of ensuring the diagnose. Management of children with DSD are focusing on gender determination, hormone support therapy and surgical management. On the other hand, Children with XY genotype should be raised as a boy however if there is no responsive evidence in administration of androgen the children should be raised as a girl. Subsequent to prescribe the gender of the children, surgical management is a required treatment for removing unnecessary genital afterward. Keywords: Disorders of Sex Development, DSD, 46 XY DSD